2022
DOI: 10.1007/s12026-022-09275-y
|View full text |Cite
|
Sign up to set email alerts
|

An overview of the biological and multifunctional roles of IL-38 in different infectious diseases and COVID-19

Abstract: Undoubtfully, the normal immune system can make a potential response to variable pathogens and neutralize or kill them depending on the type of infection through innate and acquired immunity. Cytokines have poly-peptide nature and are considered as signaling molecules that could amplify or alleviate immune responses besides their other biological functions. Interleukin 38 (IL-38) is a member of the IL-1 family cytokine that, however, its anti-inflammatory role has been observed in different autoimmune diseases… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 50 publications
(127 reference statements)
0
4
0
Order By: Relevance
“…Wang et al 50 showed elevated level of IL‐38 in patients with chronic hepatitis B, suggesting that IL‐38 could be used as a biomarker for liver hepatitis infection and liver injury 51 . Fazeli et al 52 reported that the level of IL‐38 was higher in healthy subjects than treated HCV‐infected patients, and HCV‐infected patients with higher levels of IL‐38 indicated less liver damage. In sepsis mice model, the level of IL‐38 increased and IL‐38 could prolong the survival of mice 53 .…”
Section: Role Of Ll‐38 In Related Diseasesmentioning
confidence: 99%
“…Wang et al 50 showed elevated level of IL‐38 in patients with chronic hepatitis B, suggesting that IL‐38 could be used as a biomarker for liver hepatitis infection and liver injury 51 . Fazeli et al 52 reported that the level of IL‐38 was higher in healthy subjects than treated HCV‐infected patients, and HCV‐infected patients with higher levels of IL‐38 indicated less liver damage. In sepsis mice model, the level of IL‐38 increased and IL‐38 could prolong the survival of mice 53 .…”
Section: Role Of Ll‐38 In Related Diseasesmentioning
confidence: 99%
“…Previous studies reported the anti-inflammatory effects of IL-38 [ 16 ], and its expression can induce macrophage activities in the efferocytosis process [ 17 ]. In this study, the gene expression level of Il-38 in macrophages demonstrated a significant increase only when M1 and M2 were indirectly co-cultured with MSCs and the Il-38 increase was more evident in M1 than in M2 ( p values for main effects of macrophage types [M0/M1/M2] and experimental conditions [no MSCs/+ young MSCs/+ aged MSCs] and their interaction: <0.0001, <0.0001, <0.0001, respectively; two-way factorial ANOVA).…”
Section: Resultsmentioning
confidence: 99%
“…Low levels of IL-37 have been found in patients with COVID-19, especially those who are severely ill (Ahmed and Ad'hiah, 2021;Li et al, 2021). IL-38 is an additional cytokine of the IL-1 family of cytokines that exhibit anti-inflammatory effects in a number of inflammatory, autoimmune and infectious diseases (Fazeli et al, 2022). In COVID-19 although not well explored, IL-38 has been the subject of controversy with one study reporting increased systemic levels in patients compared to controls , and another study showing no significant differences between patients and controls (Al-bassam et al, 2022).…”
Section: Introductionmentioning
confidence: 99%